Genetic counseling for congenital heart disease – Practice resource of the National Society of Genetic Counselors. Issue 1 (12th September 2021) - Ison, Hannah E.; Griffin, Emily L.; Parrott, Ashley; Shikany, Amy R.; Meyers, Lindsay; Thomas, Matthew J.; Syverson, Erin; Demo, Erin M.; Fitzgerald, Kristi K.; Fitzgerald‐Butt, Sara; Ziegler, Katie L.; Schartman, Allison F.; et al.
Abstract: Congenital heart disease (CHD) is an indication which spans multiple specialties across various genetic counseling practices. This practice resource aims to provide guidance on key considerations when approaching counseling for this particular indication while recognizing the rapidly changing landscape of knowledge within this domain. This resource was developed with consensus from a diverse group of certified genetic counselors utilizing literature relevant for CHD genetic counseling practice and is aimed at supporting genetic counselors who encounter this indication in their practice both pre‐ and postnatally.